Analisis Kualitas Interaksi Pembelajaran Matematika Realistik Pada Latihan Mengajar Mahasiswa Berdasarkan Observasi Dosen - Kumanireng, Lusia Bince (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study focuses on analyzing the quality of RMR interactions during student teaching practice. The study used a qualitative approach with a case study design. The research methods used were systematic observation and reflective interviews. Data were analyzed using Classroom Interaction Analysis techniques modified for RMR needs. This study was conducted in the Mathematics Education Study Program, Faculty of Teacher Training and Education, Larantuka Institute of Teacher Training and Technology. The subjects of this study were 10 sixth-semester students taking the realistic mathematics course. Subjects were selected using a purposive sampling technique. The research objects covered three main aspects: Quality of Learning Interactions; Implementation of RMR Principles; and Questioning Skills. Data collection in this study was carried out through Structured Participatory Observation; Semi-Structured Interviews; and Document Analysis. The research instruments used were Observation Sheets; Interview Guidelines; and Field Notes. The collected data were analyzed using the Miles, Huberman, and Saldaña model, which consists of three interactive stages: Data Condensation; Data Presentation; Verification and Conclusion Drawing. The results of the study show that, in the aspect of the quality of learning interactions, the majority of students have been able to create learning interactions that are in the good category; the aspect of Implementation of Realistic Mathematics Learning Principles is known, the Use of Context achieved the highest score of 4.5 while the Student Contribution item achieved the lowest score of 2.9 and at the Formalization stage obtained a relatively low score of 3.1; and the aspect of Student Question Quality provided results, namely, for clarification questions obtained a percentage of 45%, convergent questions 35%, exploratory questions 15%, and divergent questions 5%.